Species delimitation and phylogeographic analyses in the Ectocarpus subgroup siliculosi (Ectocarpales, Phaeophyceae). Issue 1 (24th August 2016) - Montecinos, Alejandro E.; Couceiro, Lucia; Peters, Akira F.; Desrut, Antoine; Valero, Myriam; Guillemin, Marie‐Laure
Abstract : The genus Ectocarpus (Ectocarpales, Phaeophyceae) contains filamentous algae widely distributed in marine and estuarine habitats of temperate regions in both hemispheres. While E. siliculosus has become a model organism for genomics and genetics of the brown macroalgae, accurate species delineation, distribution patterns and diversity for the genus Ectocarpus remain problematic. In this study, we used three independent species delimitation approaches to generate a robust species hypothesis for 729 Ectocarpus specimens collected mainly along the European and Chilean coasts. These approaches comprised phylogenetic reconstructions and two bioinformatics tools developed to objectively define species boundaries (General Mixed Yule Coalescence Method and Automatic Barcode Gap Discovery). Our analyses were based on DNA sequences of two loci: the mitochondrial cytochrome oxidase subunit 1 and the nuclear internal transcribed spacer 1 of the ribosomal DNA. Our analyses showed the presence of at least 15 cryptic species and suggest the existence of incomplete lineage sorting or introgression between five of them. These results suggested the possible existence of different levels of reproductive barriers within this species complex. We also detected differences among species in their phylogeographic patterns, range and depth distributions, which may suggest different biogeographic histories (e.g., endemic species or recent introductions).